INNOVATION IN TOPICAL PATCH PREPARATIONS BASED ON SHALLOT EXTRACT (Allium cepa L.) AS SUPPORTIVE THERAPY MINOR WOUNDS: FORMULATION AND PHYSICAL EVALUATION - Deniyati; Andi Nur Ilmi Adriana; Syachriani; Rosdiana (Jurnal Jamu Kusuma, 2025)
A study was conducted on the formulation and evaluation of a shallot (Allium cepa L.) extract patch. The purpose of this study was to determine the formulation of a shallot extract patch that meets the preparation requirements and to determine at what concentration the evaluation results of the shallot extract patch meet the preparation requirements. The patch was prepared in three concentrations: FI (2,5%), FII (5%), and FIII (7,5%). The preparation was then evaluated using organileptic tests, pH, weight uniformity, folding resistance, patch thickness, and moisture absorption. Based on the research results, organoleptic test results of shallot patch FI, FII, and FIII have a yellow color, a slight aroma of shallots and menthol, and the texture and surface condition of FI are dry, smooth, flat, flexible, and not sticky, while FII and FIII have a texture and surface condition that is slightly wet, smooth, flat, flexible, and slightly sticky. The average weight uniformity of FI patches is 2.182, FII 2.761, FIII 3.569. The pH measurement of FI, FII, and FIII is the same, namely 6. The fold resistance of the patches is also the same, namely > 300, the thickness of FI patches is 0,80 while FII and FIII are the same, namely 0,82 and the moisture absorption capacity of FI patches is 4,76, FII 5,82 and FIII 7,47.The shallot extract patch that meets the preparation requirements is the patch preparation in FI, where all preparation evaluation results meet the specified preparation requirements.